Big Nate Blasts Off - Peirce, Lincoln (New York, New York : Balzer + Bray, an imprint of HarperCollinsPublishers, 2016)
After his fight with Randy Betancourt makes headlines in the school paper, Big Nate has a problem worse than detention on his hands.
Keywords: Conduct of life -- Juvenile fiction; Middle schools -- Juvenile fiction; Humorous Stories; Behavior -- Fiction; Middle schools -- Fiction; Schools -- Fiction